The The Effect of Work Discipline and Work Motivation on Employee Performance at Jamu Jago Joyokusumo Herbal Medicine Factory - Leni Kris Tanti (NAROTAMA UNIVERSITY, Indonesia, 2020)
This research is a survey research with a quantitative approach. The sample of this research is all employees of Jamu Jago Joyokusumo Factory Banyuwangi, amounting to 40 employees with the sampling technique using the census method. Data collection using a questionnaire while data analysis using multiple linear regression test. The results of this study indicate that: (1) Work Discipline has no partially significant effect on the Employee Performance of Jago Jago Joyokusumo Jamu Factory. This can be proven by the T test of 0.576 which is greater than 0.05. (2) Work motivation has a partially significant effect on the Employee Performance of Jago Jago Joyokusumo Jamu Factory. This can be proven by the T test of 0.000 which is less than 0.05. (3) Work Discipline and Work Motivation simultaneously have a significant effect on the Employee Performance of Jamu Jago Joyokusumo Factory Employees. This can be proven by the F test of F count 8.174 with a significant level of 0.001, so the significant value is much smaller than 0.05.